Protective effects of saffron extract and crocin supplementation on fatty liver tissue of high-fat diet-induced obese rats - Mashmoul, Maryam; Azlan, Azrina; Mohtarrudin, Norhafizah; Mohd Yusof, Barakatun Nisak; Khaza'ai, Huzwah; Khoo, Hock Eng; Farzadnia, Mehdi; Boroushaki, Mohammad Taher (BioMed Central, 2016)
Background: Saffron is the dried stigma of Crocus sativus L. flower which commonly used as a natural remedy to enhance health and even fights disease in the Middle-East and Southeast Asian countries. Methods: This study was aimed to investigate protective effect of saffron extract and crocin in fatty liver tissue of high-fat diet induced obese rats. A total of 36 healthy male ﻿Sprague Dawley ﻿rats were divided into six groups. Two groups served as controls, a normal diet (ND) and a high-fat diet (HFD). The other four groups were each supplemented with saffron extract and crocin at concentrations of 40 and 80 mg/kg body weight/day for 8 weeks. All groups except ND were fed with HFD until end of the study. At baseline, blood sample was collected for determination of levels of hepatic marker enzymes, including aspartate aminotransferase, alanine aminotransferase, alkaline phosphatise and albumin. Liver sample was collected, weighed and stained with haematoxylin and eosin for further histopathological examination. Results: Saffron extract and crocin at concentrations of 40 and 80 mg/kg had dose-dependently alleviated levels of liver enzymes and histopathological changes in diet-induced obese rat model compared to control (HFD group). Conclusion: This study suggested that saffron extract and crocin supplements have hepatoprotective effect against non-alcoholic fatty liver disease and HFD-induced liver damage.